Sistem Peringatan Dini untuk Deteksi Kebakaran pada Kebocoran Gas Menggunakan Fuzzy Logic Control - Wahyu Tara Dirgantara; Hadi Suyono; Onny Setyawati (Fakultas Teknik, Universitas Brawijaya, 2017)
Abstract—Fire accidents, due to the leakage of LPG gasses, should be avoided; therefore a systsem that can anticipate the accident is necessary. A system consisting of two sensors and three actuators is designed. MQ5 sensor served as a gas sensor to detect gas concentration of 200 – 10000 ppm. LM35 sensor served as a temperature sensor in range of -55–140. Output system consisted of a buzzer and two fans. System measurement is performed by modeling a cube for three conditions. The results show that the system created using fuzzy logic control can work on three conditions: 45 ppm is detected at 30.49 (no leakage gas), 70 ppm is detected by increasing temperature up to 31.49 (no leakage gas), leakage gas of 1200 ppm caused the decreased of the temperature to 28.13.